Habits of change an oral history of American nuns - Rogers, Carole G. (Oxford oral history series., 2011)
This collection of oral histories of American nuns captures the experiences of women whose lives over the past 50 years have been dramatically transformed. Bringing together women from more than 40 different religious communities, most of whom entered religious life before Vatican II, the book shows how their lives were suddenly turned around in the 1960s. Here these women speak of their active engagement in the events that disrupted their church and society, offering their unique perspective on issues such as peace activism, global equality for women, and the clergy sexual abuse crisis.